Visual and haptic verticality misperception and trunk control within 72 h after stroke - Pascucci Sande de Souza, Luciane Aparecida; Ferreira, Luana Ribeiro; Silva Bitencourt, Ana Carolina; Bazan, Rodrigo [UNESP]; Luvizutto, Gustavo José (Elsevier, 2021)
Introduction: Stroke patients often exhibit an altered perception of verticality, but there are no studies evaluating verticality perception in the first 72 h after stroke and its relationship with trunk control. Therefore, this study aimed to analyze visual and haptic verticality in the acute phase of stroke. Methods: This was a cross-sectional study conducted with two groups: (a) 13 individuals with stroke and (b) 12 healthy participants. We assessed verticality via the subjective visual vertical (SVV) and the subjective haptic vertical (SHV); and we measured trunk control with the Trunk Impairment Scale (TIS). We performed t-tests to compare the SVV and SHV between groups. Pearson correlation was performed between verticality tests with National Institutes of Health Stroke Scale (NIHSS) and the TIS. Results: Participants with recent stroke presented higher true and absolute SVV deviation values than did the control group. There was significant negative correlation between absolute (r = −0.57; p = 0.02) and true SVV (r = −0.54; p = 0.01) with TIS scores There was also significant positive correlation between absolute (r = 0.63; p = 0.009) and true SVV (r = 0.61; p = 0.003) with NIHSS. A significant negative correlation between NIHSS and TIS scores also was found (r = −0.80; p = 0.005). Conclusion: Individuals with acute stroke presented larger variability in their perceptions of visual verticality than did healthy controls, and verticality perceptions were positively correlated with trunk impairment.
Keywords: Stroke; Subjective haptic vertical; Subjective visual vertical; Trunk; Verticality